Understanding resiliency in coastal areas: a review paper from sociological perspectives - Mustari, Sohela; Karim, A.H.M Zehadul (Redfame Publishing, 2015)
Based on secondary data, this paper tries to identify the resiliency of coastal people. Existing literature emphasizes that resiliency means a kind of adaptation where societal members can adjust themselves to a different environment. It is also discovered in prevailing literature that resiliency as a concept is not well-described in sociology. Thus, in this review, it attempts to examine resiliency from sociological perspectives. To do this, previous research on coastal society is focused on to know their resilience capacity in detail.